The Effectiveness of Corporate Governance and Whistleblowing System on Fraud Disclosure - Handajani, Lilik; Muhsyaf, Saipul Arni; Sokarina, Ayudia (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 18 No 1 (2023)DO - 10.24843/JIAB.2023.v18.i01.p03, 2023)
There are increased corporate mechanisms for detecting fraud cases in financial institutions. This study aimed to investigate the impact of corporate governance and whistleblowing systems (WBS) on fraud disclosure. A multiple regression analysis was performed on 34 public banks listed on the Indonesia Stock Exchange (IDX) from 2016 to 2020. The findings showed that the bank's corporate governance rating significantly and negatively affects the disclosure of fraud. This implies that a better corporate governance rating increases the bank's ability to detect fraud. However, the increased violations reported through WBS mechanism did not indicate fraud following the investigation. Another finding showed that the potential for fraud in government-owned and large banks increases due to political intervention and conflicts of interest in business policymaking. Therefore, this study has practical implications for implementing a WBS in fraud violations in the banking sector. Keywords: fraud, corporate governance, whistleblowing system policy